Distribusi Plankton di Waduk Kedungombo - Krismono Krismono; Yayuk Sugianti (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The aim of this research was to know plankton distribution in Kedungombo reservoir. The research was conducted at three inlet station, (1) inlet from Kemukus mountain, (2) inlet from Kemusuk and (3) inlet from DAM in transition season (May and September, 2002), rainy season (November, 2002) and dry season (July, 2002). The result showed that the abundance of plankton organism was the highest at July (dry season) when the N:P ratio was highest.